Impact of Cryotreated and Warm Sodium Hypochlorite on Postoperative Pain in Teeth With Symptomatic Irreversible Pulpitis: A Randomized Controlled Trial - Lalfakawmi, Serena; Gupta, Alpa; Duraisamy, Arun Kumar; Abraham, Dax; Mrinalini, Mrinalini; Mane, Arjun Prakash (Journal of endodontics, 2024)
The purpose of this study was to evaluate effect of cryotreated and warm sodium hypochlorite (NaOCl) on postoperative pain in patients with symptomatic irreversible pulpitis and symptomatic apical periodontitis. Sixty-six individuals with preoperative pain scores of ≥54 mm on the Heft Parker Visual Analogue Pain Scale (HP-VAS) diagnosed with symptomatic irreversible pulpitis and symptomatic apical periodontitis as per the American Association of Endodontists guidelines in mandibular molars were included. The preparation of the access and the root canals was instrumented and irrigated in accordance with a standard protocol. Based on the temperature of the final irrigant, the root canals were then randomly assigned to 3 groups and 3% NaOCl was irrigated: control (at 25°C), cold NaOCl (2°C), and warm NaOCl (60°C) (n = 22/group). Root canal treatment was completed at the same visit. Pre- and postoperative pain assessment at 6, 24, 48, and 72 hours was conducted using the HP-VAS, and analgesic consumption was noted. Suitable statistical tests were used to analyze the data. In comparison with the other 2 groups, the cold NaOCl group had a lower HP-VAS score at all follow-up intervals. Between groups, there was a statistically significant difference in postoperative pain scores at 6 and 72 hours (P < .05). None of the subjects experienced any postoperative discomfort at 72 hours in the control and cold NaOCl groups. Patients treated with cold NaOCl as the final irrigant experienced significantly less postoperative pain at 6 hours when compared with room temperature and warm NaOCl.